2009
DOI: 10.1128/mcb.01682-08
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of the Sir3 BAH Domain Reveals Multiple Points of Interaction with Nucleosomes

Abstract: Sir3, a component of the transcriptional silencing complex in the yeast Saccharomyces cerevisiae, has an N-terminal BAH domain that is crucial for the protein's silencing function. Previous work has shown that the N-terminal alanine residue of Sir3 (Ala2) and its acetylation play an important role in silencing. Here we show that the silencing defects of Sir3 Ala2 mutants can be suppressed by mutations in histones H3 and H4, specifically, by H3 D77N and H4 H75Y mutations. Additionally, a mutational analysis dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 49 publications
2
49
0
Order By: Relevance
“…In dot1D and set1D mutants, establishment of silencing was more rapid than in wild-type cells, probably because active transcription was compromised by the hypomethylated chromatin and hence was less resistant to silencing (Osborne et al 2009). However, it may also have been caused by the better binding of Sir proteins to hypomethylated histones (Onishi et al 2007;Sampath et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…In dot1D and set1D mutants, establishment of silencing was more rapid than in wild-type cells, probably because active transcription was compromised by the hypomethylated chromatin and hence was less resistant to silencing (Osborne et al 2009). However, it may also have been caused by the better binding of Sir proteins to hypomethylated histones (Onishi et al 2007;Sampath et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Genetic suppressor studies over the course of many years suggested that the domain mediates binding of nucleosomes. Mutations that mapped to the BAH domain suppressed mutations of either the H4 tail or a patch on the nucleosome surface known as the LRS domain (Johnson et al 1990;Thompson et al 2003;Norris et al 2008;Sampath et al 2009). The BAH domain was sufficient for partial silencing when forced to dimerize, strengthening the notion that the BAH domain was sufficient for nucleosome recognition (Connelly et al 2006).…”
Section: Sir3 Protein Structurementioning
confidence: 99%
“…Mutations that block N a acetylation of Sir3 abolish silencing and impede assembly of extended silent chromatin domains (Whiteway et al 1987;Mullen et al 1989;Ruault et al 2011). Genetic studies suggested and biochemical studies proved that Sir3 N a acetylation increases the affinity of Sir3 for nucleosomes (Connelly et al 2006;Onishi et al 2007;van Welsem et al 2008;Sampath et al 2009). Crystallographic studies showed that the Sir3 modification stabilizes the surface of the Sir3 BAH domain at the nucleosome-binding interface (Arnaudo et al 2013;Yang et al 2013).…”
Section: Post-and Cotranslational Modification Of Sir3mentioning
confidence: 99%
“…First, Dot1 catalyzes the mono-, di-, and trimethylation states of H3 K79 (27,28,30,31). This particular lysine is located on the loss of rDNA silencing (LRS) face of H3, a surface whose electrostatic properties are important for association between the nucleosome and the BAH domain of Sir3 (32)(33)(34)(35)(36). H3 K79 methylation, therefore, interferes with the nucleosome's ability to adequately bind Sir3 (9).…”
mentioning
confidence: 99%